Cumulative effect of digital manufacturing techniques, preparation taper and finish line designs on the retention of aged temporary molar crowns − An in vitro study - Firas K. Alqarawi; Mohammed E. Sayed; Harisha Dewan; Fawzia Ibraheem Shaabi; Hina Naim; Manawar Ahmad; Hanan Ibrahim Hakami; Ebrahim Fihaid Alsubaiy; Areen Sultan; Saad Saleh AlResayes (Elsevier, 2024)
Objective: This study evaluated the effects of finish-line design, tooth preparation taper or total occlusal convergence (TOC), and digital production technology on the retention of provisional crowns for molars. Material and Methods:  Different taper angles (10° TOC and 20° TOC) and finish line designs (chamfer and shoulder) were used to prepare four mandibular first molar teeth. Two subgroups of the prepared teeth received temporary crowns that were either "Computer-Aided Design" and "Computer-Aided Manufacturing (CAD/CAM) milled or 3D printed. Hence, eight test groups of temporary crowns containing 10 samples each were created. Groups 1-4 were milled, and Groups 5-8 were 3D printed specimens. A consistent procedure was used to cement 80 temporary crowns. The specimens were thermocycled for a total of 5000 heat cycles, initially at 5 °C for 30 s (dwell time) and then at 55 °C for 30 s. The pull-off force necessary to remove the temporary crowns was recorded, and the tensile strength, which served as the dependent variable, was calculated. Analysis of variance (ANOVA) was used to assess the variations in retention forces among the test groups. Results:  The mean tensile strengths at maximum load [MPa] were higher in Groups 5, 6, 7, 8 (6.6 MPa, 6.91 MPa, 7.65 MPa, and 7.45 MPa respectively) as compared to the mean tensile strengths at maximum load [MPa] in Groups 1, 2, 3, 4 (2.35 MPa, 3.52 MPa, 3.21 MPa, and 2.45 MPa respectively). Conclusion: For extended periods, 3D-printed crowns with steeper preparation tapers (20° TOC) and shoulder finish lines exhibited enhanced retention.